The Limit Behavior of a Stochastic Logistic Model with Individual Time-Dependent Rates - Yilun Shang (Journal of Mathematics, 2013)
We investigate a variant of the stochastic logistic model that allows individual variation and time-dependent infection and recovery rates. The model is described as a heterogeneous density dependent Markov chain. We show that the process can be approximated by a deterministic process defined by an integral equation as the population size grows.